COVID-19-related acute kidney injury and dialysis: What are the outcomes in South Africa? - van Hougenhouck-Tulleken, Wesley George; Hussain, Muhammed; do Vale, Claudia (African Journal of Nephrology, 2021)
Introduction: Acute kidney injury (AKI) in hospitalized patients infected with COVID-19 is associated with an elevated mortality rate compared to non-infected patients (39% versus 24%). This is despite a lower prevalence of AKI in COVID-19-infected patients (17 vs 22%). The reasons are multifactorial and have been well documented in developed countries, whereas in developing countries there are scant data. Methods: This study aimed to document the mortality in COVID-19-infected South African patients who required dialysis for AKI. Exclusion criteria included any chronic kidney replacement therapy (transplantation or dialysis). A REDCap survey of South African nephrologists and nephrology fellows registered with the South African Nephrology Society was conducted. The primary outcome was all-cause in-hospital mortality, while additional points of interest included comorbidities, dialysis modality and intervention required. Univariate analysis of mortality predictors was performed. Results: The COVID-19-related AKI mortality rate was 58.9%. Significant predictors included continuous veno-venous haemodialysis therapy, invasive ventilation, use of inotropes and the presence of shock. Ischaemic heart disease, heart failure and admission to a private healthcare facility were associated with lower mortality. No significant associations were found with ethnicity, sex, hypertension, diabetes, HIV infection or the use of other modes of dialysis. Conclusions: In South African patients, we report similar outcomes in critically ill patients requiring dialysis for AKI, relative to international data. The predictors of mortality most likely reflect the severity of the illness in our patients. The data suggest that continuous veno-venous haemodiafiltration or slow low efficiency dialysis may be the preferred dialysis modalities in these patients.